Functional electrical stimulation system for a wearable-based biostimulation - Gonçalves, João (2021)
The objective of this paper is to describe the methodology and preliminary results of the development of an electrical stimulation system, for a wearable device aiming the biostimulation. The paper describes the project environment of this work, the function and importance of the functional electrical stimulation, the current development of the system and presents the preliminary results with further expectations.